2019
DOI: 10.7717/peerj.6073
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of drought effects in wheat and cucumber by the combined application of super absorbent polymer and potential biofertilizer

Abstract: Biofertilizer is a good substitute for chemical fertilizer in sustainable agriculture, but its effects are often hindered by drought stress. Super absorbent polymer (SAP), showing good capacity of water absorption and retention, can increase soil moisture. However, limited information is available about the efficiency of biofertilizer amended with SAP. This study was conducted to investigate the effects of synergistic application of SAP and biofertilizers (Paenibacillus beijingensis BJ-18 and Bacillus sp. L-56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 96 publications
(97 reference statements)
2
17
0
2
Order By: Relevance
“…For example, chitosan-immobilized aggregated Methylobacterium oryzae CBMB20 has been used as a bioinoculant to promote growth of tomato under salt stress conditions (Chanratana et al, 2019). Li et al (2019) also showed synergistic use of a Super Absorbent Polymer (SAP) along with PGPR strains of Paenibacillus beijingensis BJ-18 and Bacillus sp. L-56 to overcome salinity stress in wheat and cucumber.…”
Section: Future Prospectsmentioning
confidence: 99%
“…For example, chitosan-immobilized aggregated Methylobacterium oryzae CBMB20 has been used as a bioinoculant to promote growth of tomato under salt stress conditions (Chanratana et al, 2019). Li et al (2019) also showed synergistic use of a Super Absorbent Polymer (SAP) along with PGPR strains of Paenibacillus beijingensis BJ-18 and Bacillus sp. L-56 to overcome salinity stress in wheat and cucumber.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Seedling growth assays were performed in plastic pots (diameter of 9 cm; height of 12 cm) filled with 1 kg low nutrition-content soil. The collection and physicochemical properties of soil were described by Li et al (2019b). The treatments contained: (1) wheat seedling inoculated with Paenibacillus sp.…”
Section: Plant Culture and Collectionmentioning
confidence: 99%
“…These two effects decreased the negative influence of extreme environmental factors and native microbial competence on XT13 and XT14, possibly extending tolerance in Guinea grass longer. Recent evidence has demonstrated that the use of integrating super absorbent polymers (SAP) with PGPB in liquid cultivations is a viable stratey to mitigate the effects of drought in wheat and cucumber (Li et al 2019). In addition, other studies in China have demonstrated that poly-γ-glutamic acid (γ-PGA) synthesis by the two Bacillus subtilis and their application increased resistance to drought in maize improving growth of microbial populations Bacillus, Pseudomonas, Burkholderia, Talaromyces and Rhizopus in soil (Yin et al 2018).…”
Section: Discussionmentioning
confidence: 99%